Protective relaying principles and applications - Blackburn, J. Lewis (Electrical engineering and electronics, 1987)
Technological advances and structural changes within the electric utility industry mandate that protection engineers develop a solid understanding of the related new technologies as well as of power system operations and economics in order to function proficiently. Continuing in the bestselling tradition of the previous editions by the late J. Lewis Blackburn, Protective Relaying: Principles and Applications, Third Edition retains the fundamentals of protection relays and power system protection while incorporating new developments in the field. Thoroughly updated and revised, this third edition focuses on technological changes in the design of protective systems, the practical concerns of power system protection encountered by users, and the techniques for protecting typical facilities used in modern power systems.